Dinasti Safawiyah: Pusat Kebudayaan di Persia Abad ke-16 - Muh. Idris (Tumanurung: Jurnal Sejarah dan Budaya, 2025)
This article discusses the Fatimid Dynasty: Cultural Center in 16th Century Persia. The aim of this research is to answer the problem formulation in the research, namely: 1.) What is the background to the founding of the Safawiyah Dynasty? 2.) What was the heyday of the Safavid Dynasty like? 3.) How did the Safawiyah Dynasty decline? This research is historical descriptive-analytical library research with religious, historical and sociological approaches. The results of this research are that the Safawiyah dynasty in Persia was founded in 1501-1736 AD, starting from a tarekat movement which then developed into a political movement. The Safawiyah Order was the forerunner to the founding of the Safawiyah dynasty, the founder of this dynasty was Ismail. During its heyday, this dynasty became the center of culture in Persia in the 16th century, which can be seen from advances in politics, economics, science, architecture, arts and religion. The period of decline of this dynasty began to appear when Abbas I died, then during the era of the following sultans the condition of the Safawiyah dynasty did not show a graph of development but slowly experienced a decline which finally led to the verge of destruction in 1736 AD under the rule of Sultan Abbas III.